A bilateral comparison of lower limb strength and pirouette performance in elite female dancers - Cullen, E. K.; Hudson, P. E.; Smith, N. A. (Journal of Dance Medicine & Science, 2025)
Introduction: Traditional dance training is designed to develop a well-balanced dancer, yet laterality has the ability to impair bilateral strength and functional symmetry. The aim of this study was to investigate the effects of lateral preference on elite level dancers by conducting a bilateral comparison of lower limb strength and pirouette performance. A pirouette is an essential turning skill in dance technique, wherein multiple revolutions are completed on a single supporting leg along the longitudinal axis.